Potência do laser de baixa intensidade na viabilidade do retalho cutâneo randômico em ratos - Costa, Maíra Silva da [UNIFESP] (2009)
Background and Objectives: Potency values in low level laser therapy (LLLT) are not well defined. This present study was designed to assess the effects of LLLT with output power of 30 and 60mW, in the viability of a random skin flap in rats. Methods: Thirty six wistar rats were randomically divided in three groups: control (CG), was not irradiated; 30 mW potency (30mW) and 60 mW potency (60mW). In both treated groups a fluency of 3J/cm2 was used. Two minutes after elevation of a random pattern, cranially based, dorsal flap (4 x 10 cm), laser irradiation was applied and repeated on the first, second, third and fourth postoperative days. Percentages of flap necrosis were calculated on the seventh postoperative day. Also, four fragments of each flap were collected in order to allow determination of the percentages of vascular density, according to bidimensional method the blood vessels morphometric analysis. Statistical analysis included Wilcoxon’s test and Kruskal Wallis’ variance analysis. A significance level of 5 % was elected (p ≤ 0.005). Results: Laser treated animals presented significantly less necrosis than control rats (CG = 53 % x 30G = 24 %; p <0.05) (CG x 60G = 25 %; p < 0.05). No difference was found between laser treated animals. Also, laser treated animals presented significantly more vascular density than control rats (CG = 37 % x 30G = 57 %; p <0.05) (CG x 60G = 59 %; p < 0.05). No difference was found between laser treated animals. Conclusion: Low level laser with potency of 30 and 60mW, increased the viability of a random skin flap in rats.